Participación de la industria argentina en la Central Nuclear en Atucha y futuras - Báez, Juan Nicolás; Darnond, Luis; Fritzsche, Jürgen; Grasso, Horacio Oscar; Quihillalt, Oscar José; Sarrate, Mariano; Wortman, Oscar (Comisión Nacional de Energía Atómica; Argentina, 1972)
Fil: Báez, Juan Nicolás Comisión Nacional de Energía Atómica; Argentina